François Roffiaen's terrestrial and freshwater gastropod types in the collection of the Royal Belgian Institute of Natural Sciences - Rodrigo Brincalepe Salvador; Cedric d'Udekem d'Acoz; Maxim V. Vinarski; Yves Samyn; Barbara Mizumo Tomotani (ZooKeys)
Jean François Xavier Roffiaen (1820–1898) was a Belgian landscape painter with a profound interest in malacology. A founding member of the Société malacologique de Belgique, Roffiaen contributed several publications on molluscs. Among such studies, his 1868 paper on Swiss terrestrial and freshwater gastropods introduced 14 new taxa (species and varieties) belonging to the Clausiliidae, Discidae, Helicidae, Lymnaeidae, Valvatidae, and Viviparidae. However, Roffiaen’s malacological contributions largely faded from recognition, primarily due to the unknown whereabouts of his type material. This study revisits his work by identifying and analysing specimens from the Royal Belgian Institute of Natural Sciences (RBINS). Of the 14 taxa described by Roffiaen, type specimens for nine (including the two full species) have been recovered, enabling a reassessment of their taxonomic status as synonyms of better-known and widespread species. The serendipitous finding of these type specimens reaffirms the importance of maintaining museum collections, and the implementation of digitization programs to uncover/recover such “lost” information, enabling it to be made available to the scientific community at large.